Susceptibility of Fibromatosis Cells in Short-Term Culture to Ifosfamide: A Possible Experimental Treatment in Clinically Aggressive Cases. (1999) - Verrill, Mark W.; Coley, Helen M.; Judson, Ian R.; Fisher, Cyril
Abstract : Purpose. Deep fibromatoses are large, often rapidly growing but benign soft tissue tumours. Although surgery is the mainstay of treatment, in unremitting and aggressive cases the use of cytotoxic chemotherapy may produce objective tumour responses. Fresh tumour samples from four patients with fibromatosis were investigated as part of a study of drug resistance in soft tissue tumours. Methods. Following short-term culture of fibromatosis cells in vitro, chemosensitivity to 4-hydroperoxy-ifosfamide, the active form of ifosfamide and doxorubicin was tested. Following 72-h continuous exposure to each drug, surviving cell fraction was assessed using the lactate dehydrogenase assay. Results. MeanIC 50 values for ifosfamide and doxorubicin were 6.2 and 0.35 µmol/l, respectively. In samples of soft tissue sarcoma (STS) from the same study the meanIC 50 values for ifosfamide and doxorubicin were 14.8 and 1.69 µmol. The difference in mean ifosfamideIC 50 values for fibromatosis and STS samples was statistically significant. Discussion. We are not aware of any other report suggesting the use of ifosfamide in this condition. These observations suggest that, for patients with inoperable or progressive lesions of fibromatosis causing significant morbidity, it may be valuable to include ifosfamide in experimental treatment regimens.